1986
DOI: 10.1099/00221287-132-3-641
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Genotypes Determined by Enzyme Electrophoresis of Neisseria meningitidis Isolated from Patients with Systemic Disease and from Healthy Carriers

Abstract: Variation in nine enzymes in 152 isolates of Neisseria meningitidis from Norway (118 from blood or cerebrospinal fluid of patients with systemic disease and 34 from the pharynx of healthy carriers) was analysed by starch-gel electrophoresis. All nine enzymes were polymorphic and the number of allozymes (electromorphs) identified per locus ranged from 3 to 12, with a mean of 6.1. Among the 152 isolates, 55 unique combinations of electromorphs (electrophoretic types, ETs) were distinguished. Twenty ETs were repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 10 publications
4
73
0
Order By: Relevance
“…2(A and B); only minor variations were found between the branching orders obtained using probes derived from different genetic loci. The value of RFLP analysis for examining the relationships between the serogroups, serotypes and sero-subtypes of N. me.ningitidis is also supported by the similarity of the phylogenetic trees presented here and those obtained by ET-typing [4,21]. RFLP analysis permits classification of strains which cannot be grouped or typed with current serological reagents.…”
Section: Disciussionsupporting
confidence: 65%
“…2(A and B); only minor variations were found between the branching orders obtained using probes derived from different genetic loci. The value of RFLP analysis for examining the relationships between the serogroups, serotypes and sero-subtypes of N. me.ningitidis is also supported by the similarity of the phylogenetic trees presented here and those obtained by ET-typing [4,21]. RFLP analysis permits classification of strains which cannot be grouped or typed with current serological reagents.…”
Section: Disciussionsupporting
confidence: 65%
“…The meningococcal blood isolate (11/86) from the patient was serogroup B, serotype 15:P1.7,16 and ET-5, as the majority of the strains isolated from patients in Norway since the beginning of the present epidemic in the mid-1970s [10] has been.…”
Section: Index Casementioning
confidence: 99%
“…conventional methods of typing are generally unsatisfactory for characterizing N. meningitidis strains from carriers. Consequently, multilocus enzyme electrophoresis was employed to identify the meningococcal clones [10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently available serological typing of serogroup-A bacteria has been based on outer-membrane protein and LPS antigens (Frasch et al, 1976;Zollinger and Mandrell, 1980) but has not yielded any striking epidemiological conclusions (Olyhoek et al, 1987). Very recently, the techniques of clonal analysis (Selander et al, 1986Achtman and Pluschke, 1986) have been applied to Neisseria meningitidis (Caugant et al, 1986a andOlyhoek et al, 1987) and the results with serogroup-A organisms have revealed world-wide patterns to the epidemic waves seen since 1962 (Olyhoek et al, 1987).…”
Section: Subgroups -mentioning
confidence: 99%
“…Clonal typing methods have now been used in epidemiological studies of serogroup-A meningococci (Olyhoek et al, 1987), and of other serogroups (Caugant et al, 1986a and. The method is based on either the isoenzyme analysis of soluble cytoplasmic enzymes or on a combination of isoenzyme analysis and outermembrane-protein analysis (Achtman and Pluschke, 1986).…”
Section: Molecular Cloning and Expression Ofmentioning
confidence: 99%